Influence of Nucleating Agent on Properties of Isotactic Polypropylene - Wang, Wensheng; Zhang, Xuejun; Zhu, Ying; Liu, Ting (Asian Journal of Chemistry, 2014)
As a nucleating agent, 1,3-2,4-di(p-hydroxy)benzylidene sorbitol (DHDBS) at mass percents (0.1, 0.2, 0.3, 0.4 and 0.5 wt. %) was added into isotactic polypropylene matrix by solution/precipitation method and compression-molded method. The crystallization morphology, spherulite dimensions and crystallinity were studied by polarizing microscope, scanning electron microscope and X-ray diffraction. The result showed that 1,3-2,4-di(p-hydroxy)benzylidene sorbitol can induce a crystal and increase the degree of crystallization of isotactic polypropylene The melting peak of isotactic polypropylene analyzed by differential scanning calorimetry was raised. It explained why crystalline perfect degree of polypropylene was increased. Thermogravimetric analysis showed that adding 1,3-2,4-di(p-hydroxy)benzylidene sorbitol can improve the stability of isotactic polypropylene. Mechanical properties of isotactic polypropylene, which were measured by use of impact test enginery and micro-computer control universal test machine, were improved. The optimal amount of nucleating agent was 0.3 wt. %.